PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KETERAMPILAN PSIKOMOTORIK SISWA KELAS V MATA PELAJARAN IPAS - Yosefina Owa Meme; Maria Yuliana Kua; Ngurah Mahendra Dinatha; Yosefina Uge Lawe (Jurnal Muara Pendidikan, 2024)
This study is based on the existence of problems at SDI Rawe related to the psychomotor skills of students who are still low and have not been well developed, so students have not been active in the implementation of learning, especially IPAS subjects. This study aims to measure the psychomotor skills of students in IPAS learning through project-based learning. The type of research used is Classroom Action Research (PTK), with a research design of the Kemmis and Mac Taggart model carried out in 2 cycles. Each cycle has 4 stages: planning, implementation, observation, and reflection. The subjects in this study were 25 fifth-grade students of SDI Rawe. The data collection techniques used were observation and tests. Data collection instruments used observation sheets and psychomotor skills test sheets. The results of the project implementation in cycle I and cycle II have increased by 32%, as seen from the percentage of student activeness of 48%, which has increased by 80%. Thus it can be concluded that project-based learning can improve the psychomotor skills of students at SDI Rawe class V in IPAS subjects.